Taxonomy of Euschizomerus Chaudoir 1850 (Coleoptera: Carabidae: Panagaeinae) from India with a new species and new synonym - Jithmon, V.a.; Thomas, Sabu K. (Zootaxa, 2018)
Description of new species Euschizomerus devagiriensis sp. nov. from south India, synonymisation of Euschizomerus schuhi Kirschenhofer, 2000 with E. indicus Jedlicka, 1955, redescriptions and new records of the earlier reported Indian species with a key to the species are provided.